Glucocorticoid Exposure of Preimplantation Embryos Increases Offspring Anxiety-Like Behavior by Upregulating miR-211-5p via Trpm1 Demethylation - Yuan, Hong-Jie; Han, Xiao; Wang, Guo-Liang; Wu, Jia-Shun; He, Nan; Zhang, Jie; Kong, Qiao-Qiao; Gong, Shuai; Luo, Ming-Jiu; Tan, Jing-He (Frontiers in Cell and Developmental Biology, 2022)
Most studies on mechanisms by which prenatal stress affects offspring behavior were conducted during late pregnancy using in vivo models; studies on the effect of preimplantation stress are rare. In vivo models do not allow accurate specification of the roles of different hormones and cells within the complicated living organism, and cannot verify whether hormones act directly on embryos or indirectly to alter progeny behavior. Furthermore, the number of anxiety-related miRNAs identified are limited. This study showed that both mouse embryo culture with corticosterone (ECC) and maternal preimplantation restraint stress (PIRS) increased anxiety-like behavior (ALB) while decreasing hippocampal expression of glucocorticoid receptor (GR) and brain-derived neurotrophic factor (BDNF) in offspring. ECC/PIRS downregulated GR and BDNF expression by increasing miR-211-5p expression via promoter demethylation of its host gene Trpm1, and this epigenetic cell fate determination was exclusively perpetuated during development into mature hippocampi. Transfection with miR-211-5p mimic/inhibitor in cultured hippocampal cell lines confirmed that miR-211-5p downregulated Gr and Bdnf. Intrahippocampal injection of miR-211-5p agomir/antagomir validated that miR-211-5p dose-dependently increased ALB while decreasing hippocampal GR/BDNF expression. In conclusion, preimplantation exposure to glucocorticoids increased ALB by upregulating miR-211-5p via Trpm1 demethylation, and miR-211-5p may be used as therapeutic targets and biomarkers for anxiety-related diseases.